Hydrogen Production by Dark Fermentation Process: Effect of Initial Organic Load (2023)
The treatment of residual biomass through the dark fermentation (DF) process is presented as a sustainable alternative, where bio-hydrogen is produced, which has a high energy potential, and bio-based sub-products. Consequently.